Wave Energy Resource and Complementarity with Wind and Solar for Madeira – Calculating the Optimal 100% Renewable Mix (Proceedings of the European Wave and Tidal Energy Conference, 2025)
The Portuguese coastline and islands have some of the best wave energy resource in Europe, and the Portuguese Government has set a target of 200MW of wave energy deployed by 2030. Madeira in particular is an archipelago with very strong wave resource, due to its location in the Atlantic Ocean, but with very deep waters which could limit the technical and economic feasibility of wave energy deployments.Modelled hourly timeseries of wave, wind and solar power production have been created for sites around Madeira with suitable water depths (up to 150m) through open-source renewable resource data, namely Copernicus Marine Service and NASA MERRA reanalysis. The wave data in particular has the novelty of being developed with the power matrix of an active wave energy developer. The CorPower Ocean power matrix is used to convert hourly wave height and period data into generation profiles. CorPower are currently demonstrating a full scale wave energy converter in Portuguese waters, at the grid-connected Aguçadoura test site, north of Porto.A comparison of the complementarity of wave energy profiles with the wind and solar profiles from existing developments on Madeira show a Pearson correlation coefficient of +0.36 between the wave and wind profiles and -0.08 between the wind and solar profiles. These low correlations indicate complementary resources which can be available at different times. The correlation coefficient between the wind and wave profiles increases to a maximum after 8-16 hours time lag, indicating the potential use of wave energy in balancing the electricity system for hours and days after wind resource has dropped. Five different metrics are used to show the complementarity, variability and persistence of wave, wind and solar profiles in this analysis.Further to this, a power systems optimization study has been developed using these same resource data inputs. Using open source software, Python for Power Systems, an optimization model has been created to investigate the cost optimal 100% renewable energy mix based on renewable availability profiles in Madeira. Scenario analysis is used to explore and compare renewable mixes which include wave energy, and those only comprised of wind and solar PV.Including wave energy as a candidate alongside wind and solar, to meet a 500MW fixed 24/7 renewable energy demand, produces multiple system benefits compared with a scenario which only has wind and solar as candidate generators. By including wave energy within the mix, the renewable overcapacity is reduced by 50%, the total system cost is reduced by 8% and the battery capacity requirement is more than halved. Comparing multiple years of renewable resource data for this analysis demonstrates consistent results in which wave profiles provide system benefits in addition to wind and solar, year on year.Although the main focus of this study is Madeira, this paper also discusses the potential for wave energy across other Atlantic islands such as the Azores and the Canary Islands, and how transferable the complementarity and optimization analyses are between these regions.